1977
DOI: 10.1002/dev.420100410
|View full text |Cite
|
Sign up to set email alerts
|

Position discrimination in the salamander, Ambystoma tigrinum

Abstract: Twenty larval tiger salamanders (Ambystoma tigrinum) were collected from a playa lake in West Texas and maintained in the laboratory for 7 days prior to the beginning of position training. Ten subjects in the larval state were trained on a position problem in a T-maze for 5 trials per day to a criterion of 80% correct responses, using a self-correction procedure. Following metamorphosis to the adult stage, these subjects were tested for retention. The remaining 10 subjects were allowed to metamorphose prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Only few studies deal with the problem of retention of larval experience beyond metamorphosis. FLOWER (1927) observed that Salamandra salamandra forgets larval prey experience during metamorphosis, whereas in other urodele species retention of certain larval experience beyond metamorphosis was observed (HERSHKOWITZ and SAMUEL 1973;SCHWARTZ and COGAN 1977). Possibly, the degree to which larval experience determines behavior after metamorphosis varies among species, and may depend on the extent to which the mode of life is changed.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies deal with the problem of retention of larval experience beyond metamorphosis. FLOWER (1927) observed that Salamandra salamandra forgets larval prey experience during metamorphosis, whereas in other urodele species retention of certain larval experience beyond metamorphosis was observed (HERSHKOWITZ and SAMUEL 1973;SCHWARTZ and COGAN 1977). Possibly, the degree to which larval experience determines behavior after metamorphosis varies among species, and may depend on the extent to which the mode of life is changed.…”
Section: Discussionmentioning
confidence: 99%